Aberrant activation of sphingosine-1-phosphate signalling in nasopharyngeal carcinoma / Lee Hui Min - Lee, Hui Min (2017)
Nasopharyngeal carcinoma (NPC) is a highly metastatic disease arising from the epithelial cells in the nasopharynx that is exceptionally prevalent in Southeast Asia and Southern China. NPC is classified into keratinising and non-keratinising carcinoma in which non-keratinising NPC is consistently associated with Epstein-Barr virus (EBV) infection; close to 100% of cases in endemic regions are EBV-associated. More than 70% of NPC patients present with late stage disease and existing treatment for advanced disease is limited to concurrent chemo-radiotherapy. Approximately 30% of these patients develop distant metastases post therapy and due to the location of tumours in close proximity to many vital organs in the head and neck region, most NPC survivors have an impaired health-related quality of life. A better understanding of the molecular basis of NPC is required to inform innovations in the therapeutic approach. The present study was designed to investigate the biological significance of sphingosine-1-phosphate (S1P) signalling in the pathogenesis of NPC and the contribution of EBV to the dysregulation of this pathway. S1P is a bioactive lipid produced by the activity of sphingosine kinases (SPHKs), which signals through a family of five G protein-coupled receptors, termed S1P receptors 1-5 (S1PR1-5), to trigger multiple pathways that regulate important biological processes. There is now compelling evidence to show that the SPHKs/S1P/S1PRs axis is a novel and attractive therapeutic target in cancer. High expression of SPHK1 has been shown in primary NPCs and therefore, elevated levels of S1P are likely to be present in NPC cells. The present study showed that treatment of NPC cells with exogenous S1P enhanced the migration and invasion and these effects were accompanied by the activation of AKT. Focusing on the migratory phenotype, shRNA knockdown of SPHK1 resulted in a reduction in the levels of phosphorylated AKT and inhibition of cell migration. Furthermore, re-analysis of two published microarray datasets revealed the over-expression of S1PR3 in primary NPC tissues compared to non-malignant nasopharyngeal epithelium. Knockdown of S1PR3 inhibited the activation of AKT and the S1P-induced migration of NPC cells. The expression of constitutively active AKT was able to partially rescue the repressive effects of the knockdown of SPHK1 and S1PR3 on cell migration. In addition, the only EBV-positive NPC cell line, C666-1, expressed the highest levels of SPHK1 and S1PR3 compared to a panel of seven EBV-negative NPC cell lines. To elucidate the contribution of EBV to the deregulation of S1P signalling, the present study demonstrated that EBV infection or ectopic expression of EBV-encoded latent genes (EBNA1, LMP1 or LMP2A) can upregulate the expression of SPHK1 in NPC cells. Taken together, the results of the present study show for the first time that S1P induces NPC cell migration by activating AKT through S1PR3, and point to a central role of EBV infection in mediating the oncogenic effects of S1P in this disease. Therefore, targeting S1P signalling could be a promising therapeutic intervention for NPC.